Morphological Variations of Hippocampal Formation in Epilepsy - J Gordon Millichap (Pediatric Neurology Briefs, 2013)
Researchers at Hospital Sao Paulo and other centers in Brazil compared the hippocampal formation (HF) morphology of healthy asymptomatic individuals (n=30) with that of patients with mesial temporal lobe epilepsy and hippocampal sclerosis (MTLE-HS)(n=68), of patients with malformations of cortical development (MCD)(n=34), and of patients with morphological HF variations without other structural signs (pure MVHF)(n=12).